Study of short-lived resonances with the ALICE Experiment at the LHC - Uysal, Ayben Karasu (IOP PUBLISHING LTD, 2012)
The study of short-lived resonances allows the investigation of the collision dynamics and of the properties of the hot and dense medium created in high energy collisions. Moreover it is interesting to address the topics of the strangeness production by the analysis of strange resonances. First measurements of the phi(1020), Lambda*(1520), Xi*(892), E *(1530) and doubly charged Delta(1232) resonances in pp collisions at a center of mass energy of 7 TeV with the ALICE apparatus at the LHC are presented. Thermal model predictions of particle ratios in proton-proton collisions are shown.
Keywords: EVENT; MODEL; Physics